New approach to timelike Bertrand curves in 3-dimensional Minkowski space - Erdem, H.A.; Uçum, A.; İlarslan, K.; Camcı, Ç. (Carpathian Mathematical Publications, 2023)
In the theory of curves in Euclidean $3$-space, it is well known that a curve $β $ is said to be a Bertrand curve if for another curve $β^{\star}$ there exists a one-to-one correspondence between $β $ and $β^{\star}$ such that both curves have common principal normal line. These curves have been studied in different spaces over a long period of time and found wide application in different areas. In this article, the conditions for a timelike curve to be Bertrand curve are obtained by using a new approach in contrast to the well-known classical approach for Bertrand curves in Minkowski $3$-space. Related examples that meet these conditions are given. Moreover, thanks to this new approach, timelike, spacelike and Cartan null Bertrand mates of a timelike general helix have been obtained.